Exit ‘Presentation Scene’, Fiat ‘Temple Entrance Scene’. How to Rethink this Emblematic Scene of the First Half of the Second Millennium BC in Light of Textual Records and the Theory of Emotions - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
Can the seals from the third dynasty of Ur and Old Babylonian periods called ‘presentation scene’ seals be analyzed in a new way? And what do these seals mean? This article tries to answer these questions, starting from a detail of the seals’ iconography, the royal inscriptions and the theory of emotions.